Preparation method of TEMTP
By using composite sulfuric acid catalyst and supercritical CO2 in a three-stage microchannel reactor, the existing problems of harsh reaction conditions, low product purity and poor stability during the synthesis of polyperoxalane compounds are solved, and an efficient and environmentally friendly TEMTP preparation method is achieved.
Patent Information
- Application Number
- CN202510340033.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-21
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-21
AI Technical Summary
The existing polyperoxalane compounds have problems such as harsh reaction conditions, low product purity and poor stability during the synthesis process, which limits their application in industry and increases production costs and environmental burden.
The three-stage microchannel reactor design is adopted, combined with composite sulfuric acid catalyst and low temperature temperature control technology, and the selectivity and mass transfer efficiency are improved through high shear mixing and photocatalysis, and supercritical CO2 is used to replace toxic solvents and achieve green separation.
It significantly improves the purity, selectivity and stability of the product, reduces energy consumption and environmental burden, and achieves efficient, safe, and environmentally friendly continuous production.
Smart Images

Figure CN119841804A_ABST
Abstract
Description
Technical Field
[0001] The invention discloses a method for preparing TEMTP, and belongs to the technical field of organic cyclic peroxides. Background Art
[0002] 3,6,9-Triethyl-3,6,9-trimethyl-1,4,7-triperoxynonane (TEMTP) is a typical organic cyclic peroxide with high activity and oxidizing properties and is easy to decompose. Due to the presence of peroxide bonds and a high oxygen content in its molecular structure, TEMTP can be used as a free radical initiator and participate in oxidation reactions, and is widely used in organic synthesis, polymer materials, fuel additives and other fields. However, the existing polyperoxyalkane compounds have many problems in the synthesis process, such as harsh reaction conditions, low product purity, and poor stability. These problems not only limit their application in industry, but also increase production costs and environmental burdens. Therefore, it is of great significance to develop an efficient, mild and environmentally friendly preparation method.
[0003] The existing methods for preparing organic peroxides still have certain deficiencies in terms of reaction conditions, product purity, stability and environmental friendliness. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art, provide a method for preparing TEMTP of an organic peroxide which optimizes the synthesis process, reduces the severity of reaction conditions, improves the purity and stability of the product, reduces the environmental burden, and meets the requirements of industrial production for efficient and environmentally friendly organic peroxides.
[0005] The technical solution adopted by the present invention to solve the technical problem is: a preparation method of TEMTP, comprising the following steps: in a three-stage microchannel reactor, an organic ketone and hydrogen peroxide are subjected to a synthesis reaction under the catalysis of a composite sulfuric acid catalyst, and the oil phase separated from the system after the reaction is 3,6,9-triethyl-3,6,9-trimethyl-1,4,7-triperoxynonane; wherein the reaction temperature is 10°C to 35°C; the total reaction time in the three-stage microchannel is 3.5h to 6h; the feed molar ratio of the organic ketone to the hydrogen peroxide is 0.5 to 2.5:1; the organic ketone is selected from one or more of butanone and its homologues; The three-stage microchannel reactor is as follows: the first-stage channel is a 2±0.2 mm serpentine structure for high shear mixing; the secondary channel is a 1±0.2 mm spiral structure with TiO2-Ag nano-photocatalyst loaded on the inner wall; and the final channel is a 2±0.2 mm straight channel into which supercritical CO2 is introduced.
[0006] The present invention realizes efficient synthesis of TEMTP through the coordinated design of three-stage microchannel reactor (the first-stage serpentine channel realizes high shear mixing, the secondary spiral channel loads TiO2-Ag nanophotocatalyst to improve selectivity, and the final straight channel introduces supercritical CO2 to enhance mass transfer and green separation), combined with composite sulfuric acid catalyst and low-temperature temperature control technology. The process uses organic ketones and hydrogen peroxide as raw materials, and continuously flows through microchannels to avoid local overheating, significantly improving the purity and stability of the product; at the same time, supercritical CO2 is used to replace toxic solvents and photocatalysis to reduce by-products, which has both green environmental protection and economic advantages, while reducing energy consumption and safety risks, and realizing continuous production with high yield and high structural controllability, providing an efficient, safe and environmentally friendly solution for industrial applications.
[0007] The synthetic reaction route of the present invention is: .
[0008] Preferably, in the above-mentioned preparation method of TEMTP, the length of the primary channel is 1000±100 mm, and rapid and uniform mixing of the raw materials is achieved through high shear force. The loading amount of the TiO2-Ag nano-photocatalyst loaded on the inner wall of the secondary channel is 8mg / cm²~12mg / cm², and 365nm ultraviolet light irradiation is additionally performed, and the reaction activation energy is effectively reduced under 365nm ultraviolet light irradiation.
[0009] The TiO2-Ag nano-photocatalyst is a customized impregnation-calcination catalyst of the present invention, and the core steps include impregnation, drying and calcination: first, the TiO2 carrier (such as Degussa P25) is dispersed in a solvent, and after ultrasonic treatment to eliminate agglomeration, a silver nitrate solution is added dropwise according to the target loading amount (2.5wt%), and stirred for 4-12 hours under acidic conditions (pH≈3-5) to allow Ag to + Uniformly adsorbed on the TiO2 surface; then dried at 60℃~80℃ under normal pressure to remove the solvent and avoid Ag + Local enrichment; finally, the dried sample is placed in a muffle furnace, heated to 300℃~400℃ (below 400℃ to maintain the anatase phase) at a rate of 2℃ / min~5℃ / min, and calcined in air or inert atmosphere for 2~4 hours to decompose AgNO3 into nanosilver particles and stably load them on the TiO2 surface. This method has low preparation cost and is suitable for large-scale production. TiO2-Ag nanophotocatalysts prepared by other methods can also achieve similar catalytic effects.
[0010] Preferably, in the above-mentioned preparation method of TEMTP, the pressure of the supercritical CO2 in the final channel is set to 7.4MPa~7.8MPa. When the supercritical CO2 pressure of the final channel is set to 7.4MPa~7.8MPa, by precisely controlling CO2 in a supercritical state, the mass transfer efficiency is enhanced (using its high diffusivity and solubility to accelerate the reaction process), and the selective dissolution characteristics of the supercritical fluid for the product can be used to achieve green separation (CO2 gasification after pressure reduction causes the product to precipitate instantly, with a purity of ≥95%). At the same time, the temperature corresponding to the pressure range matches the reaction temperature, inhibiting the thermal decomposition of peroxides and free radical side reactions, and ensuring safety; in addition, the pressure slightly higher than the critical point can reduce the pressure resistance cost of the equipment, and the recycling of supercritical CO2 can reduce solvent consumption, and the TiO2-Ag photocatalyst particles remaining in the secondary channel can also self-clean the surface through the microemulsion in the supercritical system, prolonging the catalytic life, and finally realizing efficient, environmentally friendly, low-cost continuous production.
[0011] Preferably, in the above-mentioned preparation method of TEMTP, the inner wall surfaces of the three-stage microchannel reactor are all provided with super-hydrophobic interfaces formed by plasma grafting perfluorosilane to reduce material residues and reduce single batch cleaning water consumption.
[0012] Specifically, the processing steps of the super-hydrophobic interface formed by plasma grafting perfluorosilane are: The inner tube of the three-stage microchannel reactor was ultrasonically cleaned and dried with acetone and ethanol, and then an O2 / Ar mixed gas (ratio 1:1) was introduced, and the surface impurities were removed and active hydroxyl groups were generated at an ultrasonic power of 80W~120W for 10~15 minutes. Then, a 1%~2%vol ethanol solution of perfluorosilane (such as FAS-17) was atomized and introduced into the tube through a nitrogen carrier gas, and plasma grafting was performed for 30±5 minutes at a power of 100±5W and a pressure of 100Pa~200Pa, so that the perfluorosilane was decomposed into active free radicals and covalently bonded to the hydroxyl groups on the surface of the substrate to form a vertically arranged perfluoro chain monolayer. Finally, the unreacted substances were purged with nitrogen and thermally cured at 80℃~120℃ for 1 hour to enhance the interface stability, and then rinsed with ethanol and dried. The grafting density of perfluorosilane was 10±2μg / cm², completing the preparation of the superhydrophobic interface.
[0013] Preferably, in the preparation method of TEMTP, the composite sulfuric acid catalyst is a composite catalyst of ionic liquid [BMIM][HSO4] and sulfuric acid (calculated as pure sulfuric acid, concentration 50wt%~80wt%) at a mass ratio of 1:2.6~3.3, and the addition amount of the composite sulfuric acid catalyst is 1%~5% of the mass of the organic ketone. The composite sulfuric acid catalyst is an ionic liquid-acid composite system, which can reduce the amount of sulfuric acid and reduce the cost of waste acid treatment, and better balance the reaction rate through dynamic feeding to improve the space-time yield. The reaction has better selectivity, and the multi-stage gradient temperature control is used to suppress the formation of dimerization by-products, and the product selectivity is increased to more than 98.5%.
[0014] Specifically, the preparation steps of the composite sulfuric acid catalyst are as follows: 1-butyl-3-methylimidazolium bromide ([BMIM]Br) and sodium bisulfate (NaHSO4) are reacted at a molar ratio of 1:3~3.5 at 100°C~105°C for 100min~150min to obtain [BMIM][HSO4] ionic liquid; the ionic liquid and sulfuric acid are mixed in proportion to obtain the composite sulfuric acid catalyst.
[0015] The preparation of this composite sulfuric acid catalyst is through the compounding of ionic liquid [BMIM][HSO4] and sulfuric acid, which is both green and efficient: first, the ionic liquid is synthesized by mild anion exchange of [BMIM]Br and cheap NaHSO4, which is simple and low-cost; after compounding, the acidity of the ionic liquid cooperates with the strong acid of sulfuric acid to form a dynamic proton network, reducing the amount of sulfuric acid, while improving the catalytic efficiency and reaction selectivity; the recyclability of the ionic liquid (activity ≥90% after 35 cycles) and the economic ratio (sulfuric acid concentration 50wt%~80wt%) further enhance the stability of the system (decomposition temperature ≥180℃), combined with the gradient temperature control of the microchannel continuous flow to accurately suppress dimerization by-products, ensure product purity (≥99%), and achieve multiple optimizations of "efficient catalysis-low consumption and emission reduction-process compatibility".
[0016] Preferably, in the above-mentioned preparation method of TEMTP, the reaction temperature in the first-stage channel is 15±2°C, and the reaction time is 20s~40s; the reaction temperature in the secondary channel is 22±2°C, and the reaction time is 25min~35min; the reaction temperature in the final channel is 32±0.5°C, and the reaction time is 50min~70min; the feed molar ratio of the organic ketone to the hydrogen peroxide is 0.6~1.2:1.
[0017] In this reaction system, an efficient and selective reaction process is achieved through precise control of multi-stage temperature and time. First, high shear micro-mixing technology (20-40 seconds) quickly forms a homogeneous system to avoid the risk of peroxide bond breakage or explosion caused by local overheating, while reducing the self-condensation side reaction of ketones under acidic conditions, reducing by-products by 12%-18%. The secondary reaction is carried out at medium temperature (22°C), adapted to the TiO2-Ag photocatalytic activity window, and selectively activates hydrogen peroxide to generate hydroxyl radicals (·OH) under ultraviolet excitation, accurately attacking the α-H site of ketones, inhibiting non-target oxidation pathways (such as peroxyacid generation), thereby increasing the selectivity of the main reaction to more than 98.5%. The final reaction is carried out at a precise high temperature (32±0.5℃), matching the critical temperature of supercritical CO2 (31.1℃). The mass transfer efficiency is enhanced in the supercritical state, the diffusion rate is increased by 3~5 times, and the intermediate cyclization is promoted to be complete. At the same time, the temperature is strictly controlled (±0.5℃ fluctuation) to avoid thermal decomposition of peroxide (decomposition rate <0.5%).
[0018] In terms of time control, the residence time of the first-stage reaction is in the order of seconds (20-40 seconds), which satisfies the rapid nucleophilic addition of protonated ketone and hydrogen peroxide, avoids the acid-catalyzed hydrolysis side reaction caused by retention in the microchannel, and thus reduces the hydrolysis products. The secondary reaction time is 25-35 minutes, ensuring that the photocatalytic oxidation and cyclization steps are fully carried out, while extending the light contact time through the spiral channel to improve the photon utilization rate. The final reaction time is 50-70 minutes, ensuring the slow and orderly assembly of the triperoxide ring structure, using the solvation effect of supercritical CO2 to stabilize the transition state, reducing the peroxide bond breakage caused by ring tension, and ultimately ensuring the integrity of the product structure.
[0019] Preferably, in the above-mentioned preparation method of TEMTP, the reaction liquid is carried out in a pulse electric field phase separation tank during oil phase separation, and the field strength of the pulse electric field phase separation tank is set to 550±5V / cm. In the phase separation treatment stage, the reaction liquid enters the pulse electric field phase separation tank, and its field strength is set to about 550V / cm. Electric field-assisted phase separation can significantly shorten the phase separation time, and the phase separation time is shortened from about 2h to about 25 minutes; and the water content of the oil phase is reduced, and the water content of the oil phase is ≤0.3%.
[0020] Preferably, the above-mentioned preparation method of TEMTP further comprises a solvent recovery step, wherein the aqueous phase is passed through a molecular sieve adsorption tower to recover residual 2-butanone, and the waste acid solution is neutralized with magnesium oxide to generate magnesium sulfate crystals for recovery.
[0021] The present invention combines catalytic system optimization, post-processing enhancement and circular economy system design to significantly improve product yield and process environmental friendliness.
[0022] The present invention also includes a recycling system to achieve efficient resource utilization and environmental friendliness. The recycling system includes three parts: waste heat recovery, solvent recovery and wastewater treatment. The waste heat is converted into 7°C cold water by the lithium bromide unit and reused for reaction temperature control. The phase-separated water phase is recovered by a vacuum distillation-extraction tower to recover more than 98% of the remaining 2-butanone, and the waste solvent is purified by molecular distillation. The COD value of the wastewater after treatment is lower than 50 mg / L, which meets the discharge requirements of the urban pipe network. The recycling system can significantly reduce cooling water consumption and raw material procurement costs, while ensuring that the wastewater meets the discharge standards.
[0023] Compared with the prior art, the present invention has the following beneficial effects: the present invention realizes the efficient and green preparation of 3,6,9-triethyl-3,6,9-trimethyl-1,4,7-triperoxynonane through the design of a three-stage microchannel reactor, optimization of the catalytic system and strengthening of post-treatment. The method significantly improves the purity, selectivity and stability of the product, while reducing energy consumption and environmental burden, and has important industrial application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the Trigonox 301 H NMR spectrum of the oil phase in Example 1.
[0025] In the figure: 3.00 and 3.09 represent the hydrogen atoms on the two methyl groups, and the hydrogen atoms on the dimethylene group are split into 0.93 and 1.46 in the NMR spectrum.
[0026] Figure 2 This is the Trigonox 301 NMR carbon spectrum of the oil phase in Example 1.
[0027] In the figure: 1.09.65 is the split peak of the carbon atom connected to the oxygen atom due to the symmetrical structure, and the other carbon atoms are affected and the peaks are split. 2.18.13 and 8.33 correspond to two methyl carbons respectively, and 26.81 is a methylene carbon.
[0028] Figure 3 The HPLC result of the oil phase in Example 1 is shown in FIG.
[0029] In the figure: the peak at 5.225 min is 3,6,9-triethyl-3,6,9-trimethyl-1,4,7-triperoxynonane.
[0030] Figure 4 This is the HPLC result of the oil phase in Example 2.
[0031] In the figure: the peak at 5.213 min is 3,6,9-triethyl-3,6,9-trimethyl-1,4,7-triperoxynonane.
[0032] Figure 5 This is the HPLC result of the oil phase in Example 3.
[0033] In the figure: the peak at 4.75 min is 3,6,9-triethyl-3,6,9-trimethyl-1,4,7-triperoxynonane.
[0034] Figure 6 This is the HPLC result of the oil phase in Example 4.
[0035] In the figure: the peak at 4.7428 min is 3,6,9-triethyl-3,6,9-trimethyl-1,4,7-triperoxynonane. DETAILED DESCRIPTION
[0036] The present invention is described in detail below by way of examples. Unless otherwise specified, all raw materials used are commercially available.
[0037] The technical solution of the present invention is described in general below.
[0038] First, for the three-stage microchannel reactor used in the present invention: the first-stage channel is a 2±0.2mm serpentine structure, which is used to achieve high shear mixing and promote rapid and uniform dispersion of raw materials. The secondary channel is a 1±0.2mm spiral structure, and its inner wall is loaded with TiO2-Ag nanophotocatalyst to reduce the reaction activation energy under ultraviolet light irradiation. The final channel is a 2±0.2mm straight channel, which is passed through supercritical CO2, and its pressure is set to 7.4MPa~7.8MPa, and the temperature is set to 32±0.5℃ to reduce the viscosity of the material and improve the mass transfer efficiency. Furthermore, the surface of the channel is plasma-grafted with perfluorosilane to form a super-hydrophobic interface, thereby reducing material residues and reducing the water consumption of single batch cleaning.
[0039] The raw materials include 2-butanone, hydrogen peroxide and catalyst, which are first mixed in the first channel. During the mixing process, the raw materials are subjected to strong shear forces in the channel to form a uniform mixture, thereby ensuring the efficient progress of subsequent reactions. The design of the serpentine channel can effectively increase the mixing path, improve the mixing effect, and reduce the generation of by-products caused by uneven reactions.
[0040] Secondary spiral channel, the TiO2-Ag nano-photocatalyst loaded on the inner wall is fixed on the channel surface by plasma technology. The loading amount of the catalyst is about 10mg / cm², ensuring that the activation energy of the reaction can be effectively reduced under ultraviolet light irradiation. The wavelength of the ultraviolet light is set to 365nm, the power is about 100W, and the irradiation time is close to 30 minutes. Under the action of ultraviolet light, the TiO2-Ag nano-photocatalyst can reduce the activation energy of the reaction from 48kJ / mol to 34kJ / mol, thereby significantly improving the reaction rate and selectivity. The selection and loading method of the catalyst can effectively avoid the catalyst from falling off and ensure the continuity and stability of the reaction.
[0041] The use of supercritical CO2 can significantly reduce material viscosity and improve mass transfer efficiency. In specific implementation, supercritical CO2 is heated to about 32°C by a preheater before entering the straight channel, and then fed into the reactor by a high-pressure pump. In the straight channel, supercritical CO2 is mixed with the raw materials to promote the efficient reaction by reducing viscosity and improving mass transfer efficiency. The use of supercritical CO2 can also reduce the generation of by-products and improve product purity.
[0042] Furthermore, the surface of the three-stage microchannel reactor is plasma grafted with perfluorosilane to form a super-hydrophobic interface.
[0043] The specific steps of plasma treatment are as follows: first, the reactor surface is plasma cleaned to remove surface impurities; then perfluorosilane is grafted in a plasma environment, the grafting time is about 30 minutes, and the grafting power is 80W~120W. The grafting density of perfluorosilane is about 10μg / cm², forming a super-hydrophobic interface. The super-hydrophobic interface can significantly reduce the residue of materials on the reactor surface and reduce the water consumption of a single batch of cleaning. In specific implementation, the reactor is rinsed with clean water after each use. Due to the existence of the super-hydrophobic interface, the water consumption is reduced by more than 75%.
[0044] The present invention also optimizes the catalytic system, and adopts ionic liquid [BMIM][HSO4] and 80% sulfuric acid in a ratio of 1:2.6~3.3 as a catalyst. The catalytic system cooperates with a segmented temperature control process, and the reaction temperature in the first-stage channel is 15±2°C; the reaction temperature in the secondary channel is 22±2°C; and the reaction temperature in the final channel is 32±0.5°C. In particular, the ionic liquid-acid composite system can not only reduce side reactions and improve yields, but also reduce the amount of sulfuric acid used and reduce the cost of waste acid treatment. At the same time, the space-time yield is improved by dynamically feeding the balanced reaction rate.
[0045] In specific implementation, the preparation steps of the ionic liquid [BMIM][HSO4] are as follows: 1-butyl-3-methylimidazolium bromide ([BMIM]Br) and sodium bisulfate (NaHSO4) are reacted at a molar ratio of 1:3 to 3.5 at 100°C to 105°C for 100min to 150min to obtain the [BMIM][HSO4] ionic liquid. The ionic liquid and sulfuric acid are mixed in proportion to form a composite catalyst. The amount of the composite catalyst used is 5% of the total amount of the raw materials. The use of the composite catalyst product can increase the selectivity of the reaction to more than 98.5%.
[0046] The present invention also relates to the strengthening of the post-treatment process, which includes two main steps of phase separation and solvent recovery. In the phase separation stage, the reaction solution enters a pulsed electric field phase separation tank, and its field strength is set to 550±5V / cm. In the solvent recovery stage, the aqueous phase is recovered by a molecular sieve adsorption tower to recover residual 2-butanone, and the waste acid solution is neutralized with magnesium oxide to generate magnesium sulfate crystals. Among them, the electric field assisted phase separation can significantly shorten the phase separation time and reduce the water content of the oil phase.
[0047] In specific implementation, the length of the pulse electric field phase separation tank is preferably 1000 mm, the width is 500 mm, and the height is 300 mm. The reaction solution is heated to 30°C by a preheater before entering the phase separation tank, and then phase separation treatment is carried out under the action of a pulse electric field of about 550 V / cm. The frequency of the pulse electric field is 50 Hz, and the treatment time is 25 minutes. Under the action of the electric field, the oil phase and the water phase can be separated quickly, the phase separation time is shortened from 2 hours to 25 minutes, and the water content of the oil phase is reduced to less than 0.3%.
[0048] In the solvent recovery stage, the aqueous phase is recovered through a molecular sieve adsorption tower to recover residual 2-butanone. The molecular sieve adsorption tower has a tower height of 2000 mm and a diameter of 500 mm. The aqueous phase is heated to 30°C by a preheater before entering the adsorption tower, and then adsorbed by the molecular sieve in the adsorption tower. The type of molecular sieve is 3A molecular sieve, and the adsorption time is 30 minutes. The specific steps of neutralizing the waste acid liquid with magnesium oxide to generate magnesium sulfate crystals are as follows: the waste acid liquid and magnesium oxide are stirred and reacted at 30°C for 30 minutes at a molar ratio of 1:1.2, and the generated magnesium sulfate crystals are separated by centrifugation, and the purity reaches 99.2%. The recovery rate of magnesium sulfate crystals exceeds 95%.
[0049] The following are specific embodiments of the present invention. The three-stage microchannel reactor used in each embodiment has the same specifications. The first-stage channel is a serpentine structure with an inner diameter of 2 mm and a length of 1000 mm; the secondary channel is a spiral structure with an inner diameter of 1 mm and a length of 500 cm; and the final channel is a 2 mm straight channel with a length of 2000 cm. Example 1
[0050] 1. Raw materials and equipment preparation: prepare 2-butanone, hydrogen peroxide and composite sulfuric acid catalyst. The composite sulfuric acid catalyst used in this example is a catalyst prepared by mixing [BMIM][HSO4] and 80% sulfuric acid (calculated as pure sulfuric acid) at a mass ratio of 1:3. The purity of 2-butanone is 99.5%, and the concentration of hydrogen peroxide is 30%. The inner wall surface of the three-stage microchannel reactor is attached with a super-hydrophobic interface formed by plasma grafted perfluorosilane.
[0051] 2. First-stage mixing: 2-butanone and hydrogen peroxide are mixed in a mass ratio of 1:1, and a composite sulfuric acid catalyst of 2.5% of the mass of 2-butanone is added and pumped into the serpentine channel through a high-pressure pump. The mixing time is 300s, the temperature is 15°C, and a uniform mixture is formed.
[0052] 3. Secondary catalysis: The mixed raw materials are fed into the spiral channel, and the inner wall of the channel is loaded with TiO2-Ag nano-photocatalyst. The catalyst loading is 10mg / cm², the wavelength of ultraviolet light is 365nm, the power is 100W, the irradiation time is 30min, and the reaction temperature is 22℃.
[0053] 4. Final treatment: The catalytic raw materials are sent into a straight channel and introduced into supercritical CO2. The pressure is set to 7.6MPa, the reaction time is 60min, and the reaction temperature is 32℃.
[0054] 5. Phase separation treatment: The reaction liquid is heated to 30°C by a preheater, and then enters a pulse electric field phase separation tank with a field strength of 550V / cm, a frequency of 50Hz, and a phase separation time of 25 minutes. The oil phase and the water phase are separated quickly, and the water phase is recovered by a molecular sieve adsorption tower to recover the residual 2-butanone, and the waste acid liquid is neutralized with magnesium oxide to generate magnesium sulfate crystals for recovery. The obtained oil phase is 3,6,9-triethyl-3,6,9-trimethyl-1,4,7-triperoxynonane, with a water content of 0.12%, and HPLC analysis is performed. HPLC analysis shows that the actual reaction yield of this example is 95.945% when the theoretical yield is calculated based on 2-butanone. Example 2
[0055] 1. Raw materials and equipment preparation: prepare 2-butanone, hydrogen peroxide and composite sulfuric acid catalyst. The composite sulfuric acid catalyst used in this example is a catalyst compounded with [BMIM][HSO4] and 50% sulfuric acid (calculated as pure sulfuric acid) at a mass ratio of 1:2.8. The purity of 2-butanone is 99.0%, and the concentration of hydrogen peroxide is 35%. The inner wall surface of the three-stage microchannel reactor is attached with a super-hydrophobic interface formed by plasma grafted perfluorosilane.
[0056] 2. First-stage mixing: 2-butanone and hydrogen peroxide are mixed at a mass ratio of 0.6:1, and a composite sulfuric acid catalyst of 2% of the mass of 2-butanone is added and pumped into the serpentine channel through a high-pressure pump. The mixing time is 25 seconds, the temperature is 16°C, and a uniform mixture is formed.
[0057] 3. Secondary catalysis: The mixed raw materials are fed into the spiral channel, and the inner wall of the channel is loaded with TiO2-Ag nano-photocatalyst. The catalyst loading is 9mg / cm², the wavelength of ultraviolet light is 365nm, the power is 120W, the irradiation time is 28min, and the reaction temperature is 23℃.
[0058] 4. Final treatment: The catalytic raw materials are sent into a straight channel and introduced into supercritical CO2. The pressure is set to 7.5MPa, the reaction time is 65min, and the reaction temperature is 32℃.
[0059] 5. Phase separation treatment: The reaction liquid is heated to 30°C by a preheater, and then enters a pulse electric field phase separation tank with a field strength of 550V / cm, a frequency of 50Hz, and a phase separation time of 25 minutes. The oil phase and the water phase are separated quickly, and the water phase is recovered by a molecular sieve adsorption tower to recover the residual 2-butanone, and the waste acid liquid is neutralized with magnesium oxide to generate magnesium sulfate crystals for recovery. The obtained oil phase is 3,6,9-triethyl-3,6,9-trimethyl-1,4,7-triperoxynonane, with a water content of 0.1%, and HPLC analysis is performed. HPLC analysis shows that the actual reaction yield of this example is 95.886% when the theoretical yield is calculated based on 2-butanone. Example 3
[0060] 1. Raw materials and equipment preparation: Prepare 2-butanone, hydrogen peroxide and composite sulfuric acid catalyst. The composite sulfuric acid catalyst used in this example is a catalyst compounded with [BMIM][HSO4] and 80% sulfuric acid (calculated as pure sulfuric acid) at a mass ratio of 1:3.1. The purity of 2-butanone is 99.5%, and the concentration of hydrogen peroxide is 25%. The inner wall surface of the three-stage microchannel reactor is attached with a super-hydrophobic interface formed by plasma grafted perfluorosilane.
[0061] 2. First-stage mixing: 2-butanone and hydrogen peroxide are mixed at a mass ratio of 1.2:1, and a composite sulfuric acid catalyst of 3% of the mass of 2-butanone is added and pumped into the serpentine channel through a high-pressure pump. The mixing time is 35 seconds, the temperature is 14°C, and a uniform mixture is formed.
[0062] 3. Secondary catalysis: The mixed raw materials are fed into the spiral channel, and the inner wall of the channel is loaded with TiO2-Ag nano-photocatalyst. The catalyst loading is 11mg / cm², the wavelength of ultraviolet light is 365nm, the power is 100W, the irradiation time is 32min, and the reaction temperature is 21℃.
[0063] 4. Final treatment: The catalytic raw materials are sent into a straight channel and introduced into supercritical CO2. The pressure is set to 7.7MPa, the reaction time is 55min, and the reaction temperature is 32℃.
[0064] 5. Phase separation: The reaction liquid is heated to 30°C by a preheater, and then enters a pulse electric field phase separation tank with a field strength of 550V / cm, a frequency of 50Hz, and a phase separation time of 25 minutes. The oil phase and the water phase are separated quickly, and the water phase is recovered by a molecular sieve adsorption tower to recover the residual 2-butanone, and the waste acid liquid is neutralized with magnesium oxide to generate magnesium sulfate crystals for recovery. The obtained oil phase is 3,6,9-triethyl-3,6,9-trimethyl-1,4,7-triperoxynonane with a water content of 0.1%, and HPLC analysis is performed. HPLC analysis shows that the actual reaction yield of this example is 94.612% when the theoretical yield is calculated based on 2-butanone. Example 4
[0065] 1. Raw materials and equipment preparation: prepare 2-butanone, hydrogen peroxide and composite sulfuric acid catalyst. The composite sulfuric acid catalyst used in this example is a catalyst compounded with [BMIM][HSO4] and 80% sulfuric acid (calculated as pure sulfuric acid) at a mass ratio of 1:2.6. The purity of 2-butanone is 99.0%, and the concentration of hydrogen peroxide is 25%. The inner wall surface of the three-stage microchannel reactor is attached with a super-hydrophobic interface formed by plasma grafted perfluorosilane.
[0066] 2. First-stage mixing: 2-butanone and hydrogen peroxide are mixed at a mass ratio of 0.5:1, and a composite sulfuric acid catalyst of 5% of the mass of 2-butanone is added and pumped into the serpentine channel through a high-pressure pump. The mixing time is 20 seconds, the temperature is 13°C, and a uniform mixture is formed.
[0067] 3. Secondary catalysis: The mixed raw materials are fed into the spiral channel, and the inner wall of the channel is loaded with TiO2-Ag nano-photocatalyst. The catalyst loading is 2mg / cm², the wavelength of ultraviolet light is 365nm, the power is 100W, the irradiation time is 25min, and the reaction temperature is 20℃.
[0068] 4. Final treatment: The catalytic raw materials are sent into a straight channel and introduced into supercritical CO2. The pressure is set to 7.4MPa, the reaction time is 70min, and the reaction temperature is 31.5℃.
[0069] 5. Phase separation treatment: The reaction liquid is heated to 35°C by a preheater, and then enters a pulse electric field phase separation tank with a field strength of 555V / cm, a frequency of 60Hz, and a phase separation time of 20 minutes. The oil phase and the water phase are separated quickly, and the water phase is recovered by a molecular sieve adsorption tower to recover the residual 2-butanone, and the waste acid liquid is neutralized with magnesium oxide to generate magnesium sulfate crystals for recovery. The obtained oil phase is 3,6,9-triethyl-3,6,9-trimethyl-1,4,7-triperoxynonane, with a water content of 0.1%, and HPLC analysis is performed. HPLC analysis shows that the actual reaction yield of this example is 94.114% when the theoretical yield is calculated based on 2-butanone. Example 5
[0070] 1. Raw materials and equipment preparation: 2-butanone, hydrogen peroxide and composite sulfuric acid catalyst were prepared. The composite sulfuric acid catalyst used in this example was a catalyst prepared by mixing [BMIM][HSO4] and 80% sulfuric acid (calculated as pure sulfuric acid) at a mass ratio of 1:3.3. The purity of 2-butanone was 99.5%, and the concentration of hydrogen peroxide was 30%. The inner wall surface of the three-stage microchannel reactor was attached with a super-hydrophobic interface formed by plasma grafted perfluorosilane.
[0071] 2. First-stage mixing: 2-butanone and hydrogen peroxide are mixed at a mass ratio of 1.5:1, and a composite sulfuric acid catalyst of 1% of the mass of 2-butanone is added and pumped into the serpentine channel through a high-pressure pump. The mixing time is 40 seconds, the temperature is 17°C, and a uniform mixture is formed.
[0072] 3. Secondary catalysis: The mixed raw materials are fed into the spiral channel, and the inner wall of the channel is loaded with TiO2-Ag nano-photocatalyst. The catalyst loading is 8mg / cm², the wavelength of ultraviolet light is 365nm, the power is 150W, the irradiation time is 35min, and the reaction temperature is 24℃.
[0073] 4. Final treatment: The catalytic raw materials are sent into a straight channel and introduced into supercritical CO2. The pressure is set to 7.8MPa, the reaction time is 50min, and the reaction temperature is 32.5℃.
[0074] 5. Phase separation treatment: The reaction liquid is heated to 25°C by a preheater, and then enters a pulse electric field phase separation tank with a field strength of 545V / cm, a frequency of 45Hz, and a phase separation time of 30 minutes. The oil phase and the water phase are separated quickly, and the water phase is recovered by a molecular sieve adsorption tower to recover the residual 2-butanone, and the waste acid liquid is neutralized with magnesium oxide to generate magnesium sulfate crystals for recovery. The obtained oil phase is 3,6,9-triethyl-3,6,9-trimethyl-1,4,7-triperoxynonane, with a water content of 0.1%, and HPLC analysis is performed. HPLC analysis shows that the actual reaction yield of this example is 93.434% when the theoretical yield is calculated based on 2-butanone.
[0075] Comparative Example 1 The basic process is the same as in Example 1, except that 80% sulfuric acid is used instead of the composite sulfuric acid catalyst. The obtained oil phase is subjected to HPLC analysis. HPLC analysis shows that the actual reaction yield of this example is 81.387% when the theoretical yield is calculated based on 2-butanone.
[0076] Comparative Example 2 The basic process is the same as in Example 1, except that a three-stage microchannel reactor is not used, and the material is only reacted in a serpentine microchannel reactor with an inner diameter of 2 mm without any catalyst on the inner wall, with a length of 2600 cm and a reaction time of 91 min. The obtained oil phase is subjected to HPLC analysis. HPLC analysis shows that the actual reaction yield of this example is 93.189% when the theoretical yield is calculated based on 2-butanone.
[0077] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing TEMTP, characterized in that: The method comprises the following steps: in a three-stage microchannel reactor, an organic ketone and hydrogen peroxide are subjected to a synthesis reaction under the catalysis of a composite sulfuric acid catalyst, and the oil phase separated from the system after the reaction is 3,6,9-triethyl-3,6,9-trimethyl-1,4,7-triperoxynonane; wherein the reaction temperature is 10°C to 30°C; the total reaction time in the three-stage microchannel is 1h to 2h; the feed molar ratio of the organic ketone to the hydrogen peroxide is 0.5 to 1.5:1; and the organic ketone is selected from one or more of butanone and its homologues; The three-stage microchannel reactor is as follows: the first-stage channel is a 2±0.2 mm serpentine structure; the secondary channel is a 1±0.2 mm spiral structure, with the inner wall loaded with TiO2-Ag nano-photocatalyst; and the final channel is a 2±0.2 mm straight channel, with supercritical CO2 introduced.
2. The method for preparing TEMTP according to claim 1, characterized in that: The length of the primary channel is 1000±100 mm, the loading amount of the TiO2-Ag nano-photocatalyst loaded on the inner wall of the secondary channel is 8 mg / cm²~12 mg / cm², and 365 nm ultraviolet light irradiation is additionally performed.
3. The method for preparing TEMTP according to claim 1, characterized in that: The pressure of the supercritical CO2 in the final channel is set to 7.4MPa~7.8MPa.
4. The method for preparing TEMTP according to claim 1, characterized in that: The inner wall surfaces of the three-stage microchannel reactor are all covered with super-hydrophobic interfaces formed by plasma grafted perfluorosilane.
5. The method for preparing TEMTP according to claim 4, characterized in that: The processing steps of the super-hydrophobic interface formed by plasma grafting perfluorosilane are as follows: 1) First, the reactor surface is plasma cleaned to remove surface impurities; 2) Then, perfluorosilane is grafted under a plasma environment, the grafting time is 30±5 minutes, the grafting power is 100±5W, and the grafting density of perfluorosilane is 10±2μg / cm², forming a superhydrophobic interface.
6. The method for preparing TEMTP according to claim 1, characterized in that: The composite sulfuric acid catalyst is a composite catalyst of ionic liquid [BMIM][HSO4] and sulfuric acid in a mass ratio of 1:2.6-3.3, and the addition amount of the composite sulfuric acid catalyst is 1%-5% of the mass of the organic ketone.
7. The method for preparing TEMTP according to claim 6, characterized in that: The preparation steps of the composite sulfuric acid catalyst ionic liquid [BMIM][HSO4] are as follows: 1-butyl-3-methylimidazolium bromide and sodium bisulfate are reacted at a molar ratio of 1:3~3.5 at 100°C~105°C for 100min~150min to obtain [BMIM][HSO4] ionic liquid; the ionic liquid and sulfuric acid are mixed in proportion to obtain a composite sulfuric acid catalyst.
8. The method for preparing TEMTP according to claim 1, characterized in that: The reaction temperature in the first-stage channel is 15±2°C, and the reaction time is 20s~40s; the reaction temperature in the secondary channel is 22±2°C, and the reaction time is 25min~35min; the reaction temperature in the final channel is 32±0.5°C, and the reaction time is 50min~70min; the feed molar ratio of the organic ketone to the hydrogen peroxide is 0.6~1.2:
1.
9. The method for preparing TEMTP according to claim 1, characterized in that: When the oil phase is separated, the reaction solution is carried out in a pulse electric field phase separation tank, and the field strength of the pulse electric field phase separation tank is set to 550±5V / cm.
10. The method for preparing TEMTP according to claim 1, characterized in that: The method also includes a solvent recovery step, in which the aqueous phase is passed through a molecular sieve adsorption tower to recover residual 2-butanone, and the waste acid liquid is neutralized with magnesium oxide to generate magnesium sulfate crystals for recovery.
Citation Information
Patent Citations
Preparation method of organic peroxide
CN115960026A
Cyclic peroxide initiator containing sterically hindered amine desensitizer as well as synthesis method and application of cyclic peroxide initiator
CN117229433A
Cited By
Process for preparing TEMTP through turntable extraction
CN121227827A